Pelatihan Penyusunan Modul Ajar Berpendekatan STEAM (Science Technology Engineering Art and Mathematics) untuk Membekali PCK (Pedagogycal Content Knowledge) Guru IPA SMP MGMP Kabupaten Bantul dalam Implementasi Kurikulum Merdeka - Susilowati, Susilowati; Setyawarno, Didik; Rahayu, Dita Puji (Yogyakarta State University, 2025)
This training activity aims to improve the pedagogical competence and professional competence of junior high school science teachers in Bantul Regency in compiling teaching modules using the STEAM (Science Technology Engineering Art Mathematics) approach to equip PCK (Pedagogical Content Knowledge) for science teachers in Bantul Regency (MGMP) in implementing the independent curriculum. This activity was attended by 30 junior high school science teachers in Bantul Regency. Training activities were held offline on Wednesday 26 July 2023 at SMP N 1 Pleret. The preparation stage was carried out by coordinating with the Bantul Regency Middle School Science (MGMP) in determining the time and location of the training. The evaluation stage is carried out during the training process. Based on success indicators, this service program can be implemented well. Each science teacher actively participates in compiling teaching modules using a STEAM approach. The science teacher responded very well to the activity and provided suggestions for improving further training.